2014
DOI: 10.1177/1479164114523146
|View full text |Cite
|
Sign up to set email alerts
|

HDL cholesterol levels and weight are the main determinants of subclinical atherosclerosis in the young with type 1 diabetes and suitable glycaemic control

Abstract: The aim of this study was to evaluate subclinical atherosclerosis and related factors in young type 1 diabetes (T1D) patients and healthy peers. Carotid intima-media thickness (cIMT) and anthropometric/laboratorial data were obtained for 83 T1D patients (mean age 19.5 ± 4.0 years, disease duration 9.8 ± 4.8 years) and for 36 matched healthy subjects. Considering all the participants as one group, male sex (p = 0.008), weight (p = 0.016) and T1D (p < 0.001) were positively associated with a higher cIMT. High-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…Age is well established as a predictor of CCA IMT in subjects with type 1[10,22] and type 2 diabetes[23]. In addition, weight was a positive predictor of CCA IMT in this study, independent of sex, and has been previously associated with CCA IMT in cohorts with and without diabetes[24,25]. Univariate analysis showed male sex was non-significantly associated with greater mean ( P = 0.12) and mean maximum ( P = 0.089) CCA IMT.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Age is well established as a predictor of CCA IMT in subjects with type 1[10,22] and type 2 diabetes[23]. In addition, weight was a positive predictor of CCA IMT in this study, independent of sex, and has been previously associated with CCA IMT in cohorts with and without diabetes[24,25]. Univariate analysis showed male sex was non-significantly associated with greater mean ( P = 0.12) and mean maximum ( P = 0.089) CCA IMT.…”
Section: Discussionsupporting
confidence: 62%
“…Univariate analysis showed male sex was non-significantly associated with greater mean ( P = 0.12) and mean maximum ( P = 0.089) CCA IMT. Previously it has been shown that male sex is associated with greater CCA IMT in people with diabetes[23,24]. Univariate analysis showed that smoking pack years was weakly positively associated with mean and mean maximum CCA IMT but this correlation did not persist after adjustment for age and weight.…”
Section: Discussionmentioning
confidence: 83%
“…Our present findings also conform to a previous report of significant associations between IMT progression, examined between EDIC Years 1 and 6, and conventional lipid profiles (ratio of LDL- and HDL-C, although not HDL-C per se ): however, in that study, lipoprotein subclasses were not measured [22]. Another small cross-sectional study of young participants with T1DM found that conventional HDL-C was inversely associated with carotid IMT, but again did not measure subclasses [38]. In studies of patients with T2DM or advanced CVD, conventional HDL-C and/or NMR-based HDL particle size have been significantly correlated with carotid IMT in some [33, 41] but not in others [32, 34, 36].…”
Section: Discussionmentioning
confidence: 89%
“…Among observational studies addressing the role of lipids/lipoproteins in macrovascular complications in T1DM [8, 17, 18, 38], only a few have examined associations with carotid IMT [8, 38]. We previously reported cross-sectional associations of NMR-determined LDL subclasses, conventional LDL-C, and apolipoprotein B (ApoB) levels with internal carotid IMT in both men and women; while for common carotid IMT, these associations were observed only in men [8].…”
Section: Discussionmentioning
confidence: 99%
“…Increased serum concentrations of small LDL were shown to be associated with multiple CVD markers, including hypertension, larger waist/hip ratio, and lower HDL-C concentration (45). HDL-C and BMI were found to be the primary determinants of carotid intimal medial thickness (CIMT) in young adults with T1D (46). Additionally, weight gain over time was related to both decreases in HDL-C and increases in CIMT in adults with TID followed in the DCCT (47).…”
Section: Discussionmentioning
confidence: 99%